SASEC vision Myanmar. (Metro Manila, Philippines Asian Development Bank, 2019)
This publication identifies regional and subregional opportunities for Myanmar to harness natural and human resources, industrial potential, and infrastructure connectivity as part of the South Asia Subregional Economic Cooperation program.It updates the Vision document of the South Asia Subregional Economic Cooperation (SASEC) program since Myanmar joined as the seventh official member in February 2017. Geographically sharing borders with the giant economies of India and the People Republic of China, Myanmar serves as a land bridge between southern, southeastern, and eastern Asia. Myanmar rich natural endowments, including oil and natural gas, and large and young labor force are also strategic advantages for regional cooperation and inclusive and sustainable growth.
Keywords: International economic integration; Agriculture -- Myanmar -- Economic conditions; Industry and trade -- Myanmar; Electronic books